2021
DOI: 10.1111/ppe.12850
|View full text |Cite
|
Sign up to set email alerts
|

Household pesticide exposures and infant gross motor development in the MADRES cohort

Abstract: Background The development of motor skills in infancy is a vital neurodevelopmental milestone. Although previous studies have explored the neurotoxic effects of agricultural pesticides on infants’ motor development, limited research has examined early postnatal household pesticide use on infants’ motor development, particularly among urban communities. Objective This study examined the association between early postnatal household pesticide use and infants’ gross and fine motor development at 6 months of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Most studies were conducted in California ( ) involving participants from the CHAMACOS cohort or in New York City ( ) and examined a variety of neurological health outcomes at different life stages. In terms of main effects, 25 of the 41 studies (or 61%) showed adverse effects of OP exposure on ASD, 96 , 211 213 infant development, 93 , 94 , 143 , 214 intelligence, 140 , 215 , 216 neural dynamics and executive functioning, 217 , 218 increases in abnormal reflexes, 219 , 220 inattention and internalizing behavior, 138 and tremors in both arms. 221 There were mixed results in 13 studies (or 32%).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in California ( ) involving participants from the CHAMACOS cohort or in New York City ( ) and examined a variety of neurological health outcomes at different life stages. In terms of main effects, 25 of the 41 studies (or 61%) showed adverse effects of OP exposure on ASD, 96 , 211 213 infant development, 93 , 94 , 143 , 214 intelligence, 140 , 215 , 216 neural dynamics and executive functioning, 217 , 218 increases in abnormal reflexes, 219 , 220 inattention and internalizing behavior, 138 and tremors in both arms. 221 There were mixed results in 13 studies (or 32%).…”
Section: Resultsmentioning
confidence: 99%